FENOMENA NGIRING PADA MASYARAKAT HINDU DI BALI - I Made Agus Adi Prawira; Ida Bagus Putu Eka Suadnyana (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2018)
The era of globalization makes the Hindu society experiencing moral egradation. The indicators are deviations from Hinduism. The phenomenon of one of the forms of deviation Hindu teachings today. The phenomenon which is a great gift and responsibility from the manifestation of Ida Sang Hyang Widhi, now turns into an arena to show the level of spirituality. Strangely again as a job land. This research answers the problem of how the phenomenon of ngiring Hindu society in Bali can happen. The type of research used is the type of qualitative empirical research. Data collection by literature review, observation, and interviews with competent sources and informants. The conclusion of this research is, The phenomenon of ngiringHindu society in Bali is a form of deviation of the implementation of the teachings of Hinduism. The solution needs to be given understanding to the Hindu community to improve sradha and bhakti Hindu teachings, either through: dharma discourse, religious counseling